The effects of labour tax progression under nash wage bargaining and flexible outsourcing - Erkki Koskela (Institute for the Study of Labor (IZA), 2008)
This paper studies in the presence of flexible outsourcing the effects of outsourcing costs, productivity of outsourcing, wage tax and tax exemption in an imperfectly competitive labour markets when labour unions and firms negotiate wages and the impacts of labour tax progression on domestic wage setting and employment. The wage elasticity of domestic labour demand is higher than in the case of strategic outsourcing and a decreasing function of the outsourcing cost, an increasing function both of the productivity of outsourcing and of the wage rate. With sufficiently strong (weak) labour market imperfections a lower outsourcing cost has a wage-moderating (wage-increasing) effect. Finally, increasing the degree of tax progression, to keep the relative tax burden per worker constant, has a wage-moderating effect and a positive effect on domestic employment and a negative effect on outsourcing.
urn:nbn:de:101:1-20080527218
Keywords: H22; 330; Outsourcing; wage negotiation; labour tax progression; employment; Lohnverhandlungen; Lohnsteuer; Steuerprogression; Outsourcing; Steuersenkung; Beschäftigungseffekt; Theorie